A study on the correlation between the intercanine dimension and the crown diameter of the first permanent molars - Chang, Edward; Sunico, Gerardo; Macapanpan, Luz C. (Adviser).
The crown diameter refers to the greats mesio-distal diameter of the first permanent molar and the intercaine dimensions is the distance between the tips of the canine in a straight line across the same arch. The objectives of this paper is to find out if a correlation between the intercanine dimension and the crown diameter of the first permanent molar exists among Filipinos. Three sampling groups are selected for the purpose of this seminar paper with twenty casts in each group. The results indicate that among those with naturally well-aligned teeth there is a correlation between the mesio-distal diameter and the intercanine distance. The intercanine distance can be predicted using the mesio-distal diameter of the first permanent molar and the regression function as early as the first permanent molar is measurable.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental arch; Orthodontics